3D Cell Culture: Fabrication of Hydrogel Particles of Defined Shapes Using Superhydrophobic‐Hydrophilic Micropatterns (Adv. Mater. 35/2016). Issue 35 (September 2016) - Neto, Ana I.; Demir, Konstantin; Popova, Anna A.; Oliveira, Mariana B.; Mano, João F.; Levkin, Pavel A.
Abstract : The inside front cover shows an array of microdroplets on a superhydrophobic–superhydrophilic pattern. Fluorescence microscopy images of hydrogel microparticles incorporating live cells expressing green fluorescent protein are visible in the background. These hydrogel particles are produced using the effect of discontinuous dewetting allowing for a rapid pipetting‐free fabrication of thousands of arrayed microdroplets and hydrogel microparticles with complex geometries and sizes, as reported by P. Levkin and co‐workers on page 7613.